Agnihotra: The Vedic Practice for the Purification of Environment and Modification of Human Behaviour - Kar, Sasmita (The international journal of religion and spirituality in society, 2013)
The human brain is the source of endless energy. But a very small fraction of mental faculty is used to fulfill man’s worldly desires. The faculties which remain unutilized tend to become dormant, lying more or less in some unknown corner of the mind. If the endless energy stored in the human mind was used scientifically, man would perform miracles throughout his life. Agnihotra is one of the best ways to reinforce that energy. Agnihotra is a very simple method of performing yagnya or offering oblations to fire at the transitional moments of sunrise and sunset. Sunrise and sunset are the smallest rhythmic cycles of nature and they leave their immediate effect on living beings. Various showerings of electricity and allied energies from the space cause a very subtle effect on the Agnihotra. The effect of Agnihotra on the environment is such that the latter gets a specific direction and is so vitally energized that it causes the human mind to react with love and equanimity. This paper will focus on the practice of Agnihotra, i.e. a specific way of sacrifice at the exact time of sunrise and sunset. Earthen or copper pots of specific size and shape, cow dung cake, unbroken rice smeared with pure ghee, etc. will be used for offering. Specified mantras (hymns) are to be chanted during the practice.